Genome-Wide Association Study That Identifies Molecular Markers with Freezing Resistance in Duroc Boar Sperm - Jiajun Zhang; Meicheng Li; Guangxiang Chen; Chenyu Tao; Bushe Li; Hejun Zhang; Hongyang Wang; Wenjun Wang (Animals)
Semen cryopreservation is a crucial technology in the artificial insemination of livestock and poultry. It not only contributes to the conservation of germplasm resources but also facilitates the cross-regional exchange of high-quality breeding stock. In this study, 165 Duroc boars were selected for genome-wide genotyping, and the sperm freezing/thawing motility ratio (sperm recovery rate) was used as phenotypic data for genome-wide association analysis (GWAS). Considerable individual variations in sperm recovery rates (SRRs) were detected, and the sperm structure after cyropreservation was significantly better in highly freeze-tolerant individuals compared to non-freeze-tolerant ones. The heritability of the SRR was calculated and found to be 0.199 ± 0.158, representing low heritability. Through GWAS, eight single-nucleotide polymorphism (SNP) loci and four candidate genes (SLC10A6, MYRF, GGA1, and UTRN) were identified as being significantly associated with sperm freezing tolerance. Moreover, the dominant genotypes of four SNPs were finally determined to be valuable for identifying individuals with high sperm freezing tolerance. This study reveals the heritability of the sperm recovery rate and identifies molecular markers associated with sperm freezing tolerance in Duroc boars, which is of great significance for accelerating boar genetic improvement and enhancing the economic efficiency of pig breeding industry.